1997
DOI: 10.1021/jp9720909
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg States of H4

Abstract: Energies of the 15 lowest Rydberg states of the metastable H4 cluster have been determined using Koopman's theorem at the equilibrium geometry of the parent ion, H4 +. To represent the core orbitals of H4, a 6-31G** basis set has been used at the SCF, MP2, MP4(SDTQ), CI-SD, and CI-SDT levels. The Rydberg orbitals have been modeled using a basis set analogous to that used to model the Rydberg orbitals of H3 in previous theoretical calculations. To test the validity of the calculations for the H4 molecule, ab in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…Instead, an unpaired electron was almost localized on H(1). The binding energies of H to H 3 + were calculated to be 3.0 kcal/mol (HF level) and 4.2 kcal/mol (MP4SDQ level), which are in reasonable agreement with the numeric values obtained previously. , The agreement revealed that the dynamics calculations at the HF/6-311G(d,p) level would give reasonable features of the reaction dynamics.
1 Geometrical parameters and schematic structure of the reaction system of H 4 + and H 4 .
…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Instead, an unpaired electron was almost localized on H(1). The binding energies of H to H 3 + were calculated to be 3.0 kcal/mol (HF level) and 4.2 kcal/mol (MP4SDQ level), which are in reasonable agreement with the numeric values obtained previously. , The agreement revealed that the dynamics calculations at the HF/6-311G(d,p) level would give reasonable features of the reaction dynamics.
1 Geometrical parameters and schematic structure of the reaction system of H 4 + and H 4 .
…”
Section: Resultssupporting
confidence: 85%
“…Comparison with the Previous Studies. The feature of the product vibrational and rotational states of H 2 obtained from the present dynamics calculations is in good agreement with that predicted by Pan and Borkman using static ab initio MO calculations . The present calculations strongly support the model proposed by them.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations